2017
DOI: 10.1080/03639045.2017.1298121
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability enhancement of flubendazole by developing nanofibrous solid dosage forms

Abstract: The bioavailability of the anthelminthic flubendazole was remarkably enhanced in comparison with the pure crystalline drug by developing completely amorphous electrospun nanofibres with a matrix consisting of hydroxypropyl-β-cyclodextrin and polyvinylpyrrolidone. The thus produced formulations can potentially be active against macrofilariae parasites causing tropical diseases, for example, river blindness and elephantiasis, which affect altogether more than a hundred million people worldwide. The bioavailabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…especially favourable in the field of pharmaceutical application [7][8][9][10][11][12][13][14][15][16][17][18]. Although the electrospinning (ES) is fast developing with appearance of tri-axial, coaxial, side-by-side and their combination processes [19][20][21][22] the most common and facile ES equipment is the single needle apparatus [23,24].…”
mentioning
confidence: 99%
“…especially favourable in the field of pharmaceutical application [7][8][9][10][11][12][13][14][15][16][17][18]. Although the electrospinning (ES) is fast developing with appearance of tri-axial, coaxial, side-by-side and their combination processes [19][20][21][22] the most common and facile ES equipment is the single needle apparatus [23,24].…”
mentioning
confidence: 99%
“…The manufacture of fibers was carried out at ambient temperature (25 °C). More details about HSES can be found in the literature [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that rational selection of the applied polymer can ensure the Vass et al (2020) stability of the amorphous drug in the matrix which meets the strict requirements of the pharmaceutical industry . The technology proved to be appropriate for the formation of flubendazole containing electrospun product as well (Vigh et al, 2017). Both the drug-loaded nanofibers and the tablets filled with the fibers had outstanding dissolution properties.…”
Section: Free Surface Esmentioning
confidence: 99%